2022
DOI: 10.2478/aoas-2021-0058
|View full text |Cite
|
Sign up to set email alerts
|

Dietary strategies to enrich milk with healthy fatty acids – A review

Abstract: Feed is the main factor impacting the composition and quality of milk of dairy animals. Therefore, the present review explores the effects of feed and nutrition on milk fat content and levels of healthy fatty acids (FA) in milk consumed by humans. Milk and dairy products are two main sources of healthy and unhealthy FA in human nutrition. The concentrations of FA in milk depend mainly on diets; therefore, milk FA concentrations and ratios can be greatly altered by some feeding strategies. Dietary supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 87 publications
(121 reference statements)
0
22
0
Order By: Relevance
“…It is well documented that milk fatty acids profile is highly sensitive to dietary changes [ 14 , 36 ]. Concentrations of milk fatty acids are greatly influenced by the type of fatty acids consumed by animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that milk fatty acids profile is highly sensitive to dietary changes [ 14 , 36 ]. Concentrations of milk fatty acids are greatly influenced by the type of fatty acids consumed by animals.…”
Section: Discussionmentioning
confidence: 99%
“…C. vulgaris also contains other biological active components such as antioxidants, provitamins, vitamins, pigments, a growth phytonutrient known as the C. vulgaris growth factor (CGF), unsaturated fatty acids (UFA), glycoproteins and carotenoids [ 11 ]. Experiments [ 3 , 13 ] showed that C. vulgaris improved ruminal bacterial growth and altered ruminal biohydrogenation of monounsaturated (MUFA) and polyunsaturated fatty acids (PUFA) due to their effects on ruminal microbes, especially those involved in the metabolism and biohydrogenation of fatty acids in the rumen [ 11 , 14 ]. Recently, Kholif et al [ 3 ] observed that the inclusion of C. vulgaris in the diets of lactating Boer goats improved nutrient intake and digestibility, ruminal fermentation, lactational performance and milk nutritive value; however, other researchers [ 15 ] observed weak effects on feed intake, digestibility or daily milk production when feeding C. vulgaris to lactating Finnish Ayrshire cows.…”
Section: Introductionmentioning
confidence: 99%
“…The treatments increased the fat contents in milk. Fat concentration in milk is related to diet composition and metabolic processes in the rumen, and this variable is often used as an indicator of rumen health and fiber adequacy in dairy animals [ 46 , 47 ]. The increased milk fat content may be related to increased ruminal acetate concentration, as acetate is the main precursor of fatty acid synthesis in the mammary gland [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fat concentration in milk is related to diet composition and metabolic processes in the rumen, and this variable is often used as an indicator of rumen health and fiber adequacy in dairy animals [ 46 , 47 ]. The increased milk fat content may be related to increased ruminal acetate concentration, as acetate is the main precursor of fatty acid synthesis in the mammary gland [ 47 ]. Iqbal et al [ 48 ] observed that feeding lactating cows a diet containing barley grain steeped in lactic acid increased milk fat content without affecting milk production and other variables of milk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation